The Influence of Organizational Climate and Organizational Commitment on Employee’s Performance in an Automotive Parts Manufacturer in Amata City Industrial Estate, Chonburi - Thaweepaiboonwong, Jutamard; Chaichun, Getgaew; Wongsansukcharoen , Jedsada; Noppakorn , Sirikwan (Business Administration and Management Journal Review, 2021)
The objectives of this study were: 1) to assess the level of organizational climate, organizational commitment, and employees’ performance; 2) to determine the effect of organizational climate on employees’ performance; 3) to determine the effect of organizational climate on organizational commitment; and 4) to determine the effect of organizational commitment on employees’ performance. The sample size was 400 employees working in an automotive parts manufacturing company in Amata City industrial estate, Chonburi province. The questionnaire was used as a tool for collecting data. The data was analyzed using mean, standard deviation, and structural equation modeling (SEM). The results of this study revealed that the level of organizational climate, organizational commitment, and employees’ performance were all at a high level. The results of structural equation modeling analysis indicated that organizational climate had no direct effect on the employees’ performance with statistical significance at the 0.05 level. The organizational climate had a significant effect on the organizational commitment of the employees, and the organizational commitment had a significant effect on the employees’ performance. Therefore, the organizational climate affected the employees’ performance through organizational commitment. The organizational climate and organizational commitment could explain 63.0% of the variance in the employees’ performance.